Keragaan dan Keragaman Genetik Sifat-sifat Kuantitatif Kedelai (Glycine max L. Merrill) pada Generasi Seleksi F6 Persilangan Varietas Slamet x Nakhonsawan1 - Edizon Jambormias; Surjono H. Sutjahjo; Muhammad Jusuf; , Suharsono (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
A field experiment to obtain new improved soybean varieties with higher yield and seed size was conducted by crossing Slamet Variety (high yield, small seed size) with Nakhonsawan (large seed size) in order to produce F6 selected generation. The process of selection and evaluation was conducted during a 3.5 month period, from August to December 2003 in KP IPB Sindang Barang Bogor. The pedigree selection method was used in the experiments. Data was analyzed based on information of set of total data, relatives and individually. The results showed that low performance for all traits compared to the Slamet variety except seed size and seed production traits, and higher than Nakhonsawan variety except seed size. However, genetic variances and heritabilities were high for all traits except number of branch. On the other hand, distribution of genetic variances and heritabilities on all levels of relatives were small except for the within-family F6 generations. This indicated that there was an effect of over-dominance gene action. Conclusion of analysis showed existence of two families with high seed production and seed size if compared to Slamet variety.   Key words: Soybean, selection, performance, genetic variability, and heritabilities.